Flashbulb memories: Is the amygdala central? An investigation of patients with amygdalar damage. (March 2018) - Spanhel, Kerstin; Wagner, Kathrin; Geiger, Maximilian J.; Ofer, Isabell; Schulze-Bonhage, Andreas; Metternich, Birgitta
Abstract: Flashbulb memories (FM) are a subgroup of autobiographical memories referring to the circumstances in which a person first heard of a surprising, emotionally arousing event. Patients with temporal lobe epilepsy (TLE) have been reported to be impaired in FM recall. As emotional arousal is central to FM, various authors have suggested a crucial role of the amygdala. However, to date, no studies have directly addressed this hypothesis. In this study, 33 TLE patients and 20 healthy controls (HC) were tested on an FM task twice with a minimum interval of two months. FM recall quality was measured as consistency of the answers. Patients were grouped according to the presence as well as the lateralisation of amygdalar damage, using information of brain imaging and intracranial electroencephalography-recordings. Analyses revealed that, relative to HC, patients with amygdalar damage had significantly diminished FM recall quality, whereas patients with intact amygdalae did not. Particularly patients with amygdalar damage in the non-language-dominant hemisphere performed significantly worse than HC. Findings suggest a negative influence of amygdalar damage, possibly especially in the non-dominant hemisphere, on FM retrieval quality. Given the shocking character of events evoking FM, a rapid emotion detection system involving the right (i.e. non-dominant) amygdala could be influential to FM formation. Thus, the present findings support previous, not yet examined, hypotheses concerning a crucial role of the amygdala in FM. Highlights: Flashbulb memories may be a specific subgroup of emotional autobiographical memory. Amygdalar damage was linked to impaired consistency of flashbulb memory recall. A specific role of the right (i.e. non-language-dominant) amygdala was revealed.